2018
DOI: 10.1016/j.jcmgh.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Cells Adhere to and Migrate Along the Neurons of the Enteric Nervous System

Abstract: Background & AimsIn several types of cancers, tumor cells invade adjacent tissues by migrating along the resident nerves of the tumor microenvironment. This process, called perineural invasion, typically occurs along extrinsic nerves, with Schwann cells providing physical guidance for the tumor cells. However, in the colorectal cancer microenvironment, the most abundant nervous structures belong to the nonmyelinated intrinsic enteric nervous system (ENS). In this study, we investigated whether colon cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 50 publications
3
54
0
Order By: Relevance
“…Nerve invasion was also a risk factor for patient survival in this study. The enteric neural network guides tumor cell migration, in part through the L1 cell adhesion molecule (L1CAM) and N-cadherin [ 28 ]. These results open new avenues to study the underlying mechanisms and progression of nerve invasion by CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve invasion was also a risk factor for patient survival in this study. The enteric neural network guides tumor cell migration, in part through the L1 cell adhesion molecule (L1CAM) and N-cadherin [ 28 ]. These results open new avenues to study the underlying mechanisms and progression of nerve invasion by CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blocking L1CAM decreases adherence and migration of tumor cells from colon adenocarcinoma to the nervous system showing involvement of L1CAM in perineural invasion in CRC. [ 81 ]. In our study, we showed that an increase in sLe X led to high E-selectin ligand expression and, curiously, resulted in increased L1CAM levels in SW620FUT6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…PNI, however, is believed to arise via extrinsic nerve bundles from the PNS [ 39 ]; a physical interaction between enteric neurons and CRC cells has been described. Enteric neurons express N-cadherin and L1CAM, which were identified as important molecules for the adhesion and migration of CRC cells [ 40 ]. However, deletion of these molecules did not completely abrogate PNI, suggesting that other (unknown) molecules must be involved as well.…”
Section: Nervous System Innervation In Colorectal Cancermentioning
confidence: 99%
“…Moreover, activation of AMPA-receptors on glioma cells stimulates the release of glutamate from the glioma cells themselves, thereby activating AMPA-receptors in an autocrine fashion and further activating neurons. Although there is currently no evidence for functional synapses between neurons and CRC cells, enteric neurons have been observed in close proximity to tumor cells [ 40 ]. Moreover, increased glutamate receptor expression has been associated with CRC [ 68 ].…”
Section: Nervous System Innervation In Colorectal Cancermentioning
confidence: 99%